North Eastern Council Draft Annual Plan 1985-86 - Planning Commission (Planning Commission, 1985)
The year 1985-86 also happened to be the first year of the Seventh Five year Plan period and, to chat extent, out bays proposed in the Annual Plan will have to be seen against the background of the proposals made for the Seventh Plan. In fact, outlays proposed for Seventh Plan will as for Annual Plan 1985-86 have been indicated both in the scheme details and financial station contained in the draft Seventh Plan document and details are, therefore not being given in this document. The outlay proposed for the NEC South plan is 979.31 crores and that for the year 1985-86 is Rs 185.53 crores, which works out around 1985 of the total outlay.
North Eastern Council